Religião e política: o neofundamentalismo no Brasil - Ortunes, Leandro (2019)
In recent years, there has been an increase in the participation of evangelicals in Brazilian politics. A fact that must be understood as native and desirable in a democracy. However, this adherence of religious to institutional politics is marked by a reactionary position and that, many times, clashes with the principle of secularism of the Brazilian State. Unlike the classical fundamentalism experienced by some Protestants in the Nineteenth Century, which closed itself in the face of social transformations and pluralism of ideas, the process of deprivatization of the religion described by José Casanova or return to the sacred presented by Peter Berger favored the development of neo-fundamentalism, which seeks through political institutions to set their standards in defense of traditional and Judeo- Christian values, as well as to combat government actions that clash with the Christian faith. This phenomenon already presented by Ivo Pedro Oro and Magali Cunha, stands out during the PT governments, especially during the presidential term of the Dilma Rousseff administration. Therefore, research on the relationship between religion and politics in Brazil experienced in recent years is fundamental to understand the new forms of political action and possible new conflicts that may arise. This study, in addition to the theoretical framework on conservatism, fundamentalism and its developments as "neos", also presents data on the actions of the Evangelical Parliamentary Front in the congress, between the years of 2015 and 2018, as well as the positions of the evangelical leaders in the media in defense of conservative guidelines. In addition, it contains the results of a survey carried out for three consecutive years, 2016, 2017, and 2018, in the streets of São Paulo, in order to quantify if the neoconservative ideals are assimilated by the believers and verify the representativeness index of the leaderships studied